Outcomes of microwave ablation for colorectal cancer liver metastases: A single center experience. Issue 4 (29th December 2014) - Eng, Oliver S.; Tsang, Ashley T.; Moore, Dirk; Chen, Chunxia; Narayanan, Sumana; Gannon, Christopher J.; August, David A.; Carpizo, Darren R.; Melstrom, Laleh G.
<x xml:space="preserve">Abstract</x> Background and Objectives Surgical management of colorectal cancer liver metastases continues to evolve to optimize oncologic outcomes while maximizing parenchymal preservation. Long‐term data after intraoperative microwave ablation are limited. This study investigates outcomes and patterns of recurrence in patients who underwent intraoperative microwave ablation. Methods A retrospective analysis of 33 patients who underwent intraoperative microwave ablation of colorectal cancer liver metastases from 2009 to 2013 at our institution was performed. Perioperative and long‐term data were reviewed to determine outcomes and patterns of recurrence. Results A total of 49 tumors were treated, ranging 0.5–5.5 cm in size. Median Clavien–Dindo classification was one. Median follow‐up was 531 days, with 13 (39.4%) patients presenting with a recurrence. Median time to first recurrence was 364 days. In those patients, 1 (7.8%) presented with an isolated local recurrence in the liver. Only 1 of 7 ablated tumors greater than 3 cm recurred (14.3%). Overall survival was 35.2% at 4 years, with a 19.3% disease‐free survival at 3.5 years. No perioperative variables predicted systemic or local recurrence. Conclusion Intraoperative microwave ablation is a safe and effective modality for use in the treatment of colorectal cancer liver metastases in tumors as large as 5.5 cm in size. J. Surg. Oncol. 2015 111:410–413. © 2014 Wiley Periodicals, Inc.